Informed trading around earnings and mutual fund alphas - Cai, Yu; Lau, Sie Ting (Journal of Banking & Finance, 2015)
We examine whether informed trading around earnings announcements drives mutual fund performance. The measure is motivated by prior studies arguing that a mutual fund is skilled if it buys stocks with subsequent high earnings announcement returns. We find that this measure predicts future mutual fund returns. On average, after adjusting for Carhart’s four risk factors, the top decile of mutual funds outperforms the bottom decile by 44 basis points per quarter. By decomposing fund alphas into two components in their relations to earnings, we find that this measure is only associated with earnings-related fund alphas. This measure can also be used to predict stock returns at future earnings announcements.